1999
DOI: 10.1084/jem.190.5.669
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Element Upstream of the Vγ2 Gene in the Murine T Cell Receptor γ Locus Cooperates with the 3′ Enhancer to Act as a Locus Control Region

Abstract: Transgenic expression constructs were employed to identify a cis-acting transcription element in the T cell receptor (TCR)-γ locus, called HsA, between the Vγ5 and Vγ2 genes. In constructs lacking the previously defined enhancer (3′ECγ1), HsA supports transcription in mature but not immature T cells in a largely position-independent fashion. 3′ECγ1, without HsA, supports transcription in immature and mature T cells but is subject to severe position effects. Together, the two elements support expression in imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…A previous report suggested that a DNase I hypersensitive site between V␥5 and V␥2 genes serves as a locus control region in concert with E␥ (32). Comparison between human and mouse V␥ regions demonstrated that human V␥1.8 and mouse V␥5 and human V␥4P and mouse V␥2 have sequence homology (data not shown).…”
Section: Conserved Stat Motifs In the Human And Mouse Tcr␥ Locimentioning
confidence: 82%
“…A previous report suggested that a DNase I hypersensitive site between V␥5 and V␥2 genes serves as a locus control region in concert with E␥ (32). Comparison between human and mouse V␥ regions demonstrated that human V␥1.8 and mouse V␥5 and human V␥4P and mouse V␥2 have sequence homology (data not shown).…”
Section: Conserved Stat Motifs In the Human And Mouse Tcr␥ Locimentioning
confidence: 82%
“…It has been shown previously by semi-quantitative chromatin immunoprecipitation (ChIP) assays that the TcrC γ 1 locus in Il7r -/-thymocytes is relatively inaccessible 16,33 . This conclusion was based on the fact that the J γ gene segment, the 3′ enhancer (E Cγ1 ), as well as the locus control region-like element (DNaseI hypersensistive site A, HsA 14,34 ), of the TcrC γ 1 locus are hypoacetylated. The latter two cis-acting elements are redundantly required for transcription of rearranged V γ 2, V γ 4, and V γ 3 genes, but substantially less so for the V γ 5 gene 14 .…”
Section: Il-15 Modulates Chromatin Accessibility Of V γ 5 Genementioning
confidence: 99%
“…PCR and RT-PCR assays to detect Tcrg gene rearrangements and transcripts were performed as described 14,34,35 using primers published and listed in Supplementary Table 1. LM-PCR to detect double-strand signal sequence breaks 3′ of the V γ 5 and V γ 2 gene segments were carried out as described 31,44 using primers listed in Supplementary Table 1.…”
Section: Semi-quantitative Pcr Rt-pcr and Lm-pcrmentioning
confidence: 99%
“…The separated populations were Ͼ90% pure. Nuclei prepared as described (25) from ϳ5 ϫ 10 7 Ly49A Ϫ or Ly49A ϩ cells, were incubated with varying concentrations of DNase I (Sigma-Aldrich, St. Louis, MO) for 5 min at 37°C (25). DNase I HSS in liver chromatin was assayed as described (26).…”
Section: Dnase I Hypersensitivity Assaymentioning
confidence: 99%